DETERMINATION OF APPROPRIATE TECHNIQUE ON CRYSTALLIZATION AND FRACTIONATION OF COCONUT OIL - - Mursalin; Purwiyatno Hariyadi; Eko Hari Purnomo; Nuri Andarwulan; Dedi Fardiaz (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2016)
Each kind of oil has different characteristics and physico-chemical properties. Therefore, cooling method applied during dry fractionation of oil must be specifically designed. Fractionation condition of coconut oil commonly uses the fractionation data of palm oil, soybean oil, butter milk, and other commercial oil. Therefore, a more suitable cooling method for coconut oil needs to be investigated. The study showed that there were three distinct cooling phases critical to crystallization process, i.e. initial cooling, critical cooling and crystallization phase. The initial cooling phase is a process of lowering the rejuvenated oil temperature to the temperature for the onset of oil crystallization. For coconut oil, the onset of crystallization temperature was found at 29°C. The critical cooling phase is cooling from 29°C to the crystallization temperature. Crystallization phase is a phase to maintain the oil temperature constant at a predetermined crystallization temperature. In the initial cooling phase, melted coconut oil might be cooled quickly to save time but in the critical cooling phase, it should be done with a cooling rate of less than 0.176°C/min to produce a physically stable crystal. This study has successfully formulated a typical dry fractionation for coconut oil at pilot plant scale (120 kg) and resulted in an effective cooling procedure to produce oil fractions with physico-chemical properties as expected. The conditions and essential requirements that must be managed and maintained in a dry fractionation stage of coconut oil had been identified and were known. Hence, the fractionation process for specific purposes can be designed in a more practical way.